MENGEMBANGKAN KECERDASAN MULTIPLE INTELLEGENCE ANAK USIA DINI - Ardiansyah, Ardiansyah; Moh. Alamsyah (Musawa: Journal for Gender Studies, 2021)
The golden age is a period that cannot be repeated again. This period also determines the life of a human being in the future. When learning there are aspects that experience development, namely cognitive, abstract thinking, creative thinking, social-emotional, motor, language or communication, and can also develop creativity. So from this aspect it can improve the development of children's multiple intelligences. Multiple Intelligences include verbal linguistics, logical-mathematical, visual spatial, musical, kinetic, intrapersonal, interpersonal, naturalist and existential. The purpose of this study is to analyze how multiple intelligences can be developed in early childhood. With this research, parents can recognize the intelligence of children and even direct and develop intelligence to the fullest. This research is a qualitative research with literature study. The results of this study are Multiple Intelligence in the aspect of linguistic intelligence and Interpersonal intelligence is very important to be developed in early childhood, because it becomes a bridge in developing children's intelligence, the development of linguistic intelligence provides communication and socialization skills and expresses children to the outside world, while Interpersonal intelligence provides the ability to manage emotional-social so that it becomes a controller for children in thinking and acting towards maturity.